An Experience in Building an Object-Oriented Prototype of an Advanced Hypertext System - Meira, Silvio; Albuquerque, Eduardo; Tepedino, José Fernando (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1990: Anais do IV Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1990.24173, 1990)
We discuss the design and construction of a Hypertext System (H) in the framework of object-oriented programming. The work also shows the pros and cons of the programming paradigm —from beginner to specialist levels— as observed from the practical point of view of building (and modifying) a complex system. The hypertext system used as example has an interest of its own, because of its visions, versions and mail capability among others, and is further detailed in the body of the paper.